SURCHIN' sea urchin larvae dispersal simulation - Agbayani, Rouela C. (1998)
A major means of living for most of the costal families in Bolinao, Pangasinan is the sea urchin (Tripneustes gratilia) fishery. Its collection started in the mid-seventies, though alternatingly (at intervals), until in 1988, when UPMSI started monitoring the said species that they found out that these invertebrate resources were already fully utilized or depleted. The monitoring done was part of their research of developing models for the management of marine resources. Having known the problem, they focused on the sea urchin recruitment dynamics which in turn helped in developing management schemes with regard to sea urchin collection. A dispersal model has been developed to simulate the transport of the sea urchin larvae. This somehow provided some insights or estimates about the sources of recruits that settled in some areas. Simulation of tidal forcing and monsoonal effects was also incorporated. However, the model is really insufficient as some parameters were arbitrarily set and many other problems were noted. Our project aims therefore to develop a similar model, but now, focusing more on the limitations and problems encountered in the present model. We will devise ways and means of improving the simulation of the sea urchin larval transport and provide adequate and near-to-accurate information or data about their recruitment dynamics.